Sheikh Nawawi al-Bantani’s Thoughts on The Rights and Obligations of Husband and Wife in His Book Entitled Uqūd al-Lujain fī Bayāni Huqūq al-Zaujain - Sanusi, Ahmad; Basya, Syifa Elrahmah; Ishom, Muhammad; Febriyani, Dian; Husin, Edi (al-'adalah, 2024)
Understanding the rights and obligations of husband and wife and carrying them out in a balanced manner is the main pillar for creating a family that is sakīnah mawaddah wa rahmah (peaceful, harmonious, and prosperous). Unfortunately, these rights and obligations are often ignored, resulting in various problems in the household. This research aims to find out the views of Sheikh Nawawi al-Bantani regarding the rights and obligations of husband and wife as written in his book 'Uqūd al-Lujain fī Bayāni Huqūq al-Zaujain. Apart from that, this research also tries to draw out the relevance of this view to changes in the attitudes of women members of the Da'arul Asy-ariyah taklim assembly towards their husbands in their daily household life. This research uses qualitative methods with a socio-empirical approach. The results of this research show that the study material of the 'Uqud al-Lujain book, which contains the rights and obligations of husbands and wives, has a positive influence on the mothers who are members of the study, which is marked by changes in the attitudes and behavior of wives towards their husbands from previously being disrespectful, disobedient and lacking respect for their husbands to being wives who are obedient, respectful and appreciative of their husbands. This positive attitude then makes household life more harmonious, serene, and peaceful so that a sakīnah mawaddah wa rahmah family atmosphere can be created.